2019
DOI: 10.1186/s12967-019-02159-0
|View full text |Cite
|
Sign up to set email alerts
|

Inulin-type fructans supplementation improves glycemic control for the prediabetes and type 2 diabetes populations: results from a GRADE-assessed systematic review and dose–response meta-analysis of 33 randomized controlled trials

Abstract: BackgroundCurrently, many clinical trials have shown that inulin-type fructans (ITF) supplementation is associated with glycemic control; nevertheless, the results are inconclusive. The aim of this meta-analysis of randomized controlled trials was to assess the effects of ITF supplementation on glycemic control.MethodsPubMed, EMBASE and the Cochrane Library were searched for eligible articles up to March 6, 2019. A random-effects model was used to analyze the pooled results, and the Grading of Recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 63 publications
1
50
0
4
Order By: Relevance
“…In addition, a meta-analysis showed that inulin-type carbohydrates could improve insulin resistant in T2DM, especially in obese T2DM patients [ 13 ]. Another meta-analysis included 33 RCTs which further demonstrated that inulin-type fructan (ITF) significantly reduced HOMA-IR in prediabetes or T2DM, as well as in healthy subjects [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a meta-analysis showed that inulin-type carbohydrates could improve insulin resistant in T2DM, especially in obese T2DM patients [ 13 ]. Another meta-analysis included 33 RCTs which further demonstrated that inulin-type fructan (ITF) significantly reduced HOMA-IR in prediabetes or T2DM, as well as in healthy subjects [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotic supplementation is associated with improved glycaemic control however as per with probiotic study reporting, heterogeneity in methodology is also vast resulting in inconclusive literature. Wang et al [ 146 ]., published the most comprehensive meta-analysis to date, which included 33 RCTs involving 1346 participants spread across healthy, obese and T2DM cohorts. Focusing solely on the prediabetic and T2DM cohorts, compared with the control, the relative reduction of the FBG, HbA1c levels, fasting insulin concentration and insulin sensitivity was 7.15, 7.00, 16.58, and 25.34% of their baseline values after supplementation [ 146 ].…”
Section: Prebiotics Probiotics and Synbioticsmentioning
confidence: 99%
“…Wang et al [ 146 ]., published the most comprehensive meta-analysis to date, which included 33 RCTs involving 1346 participants spread across healthy, obese and T2DM cohorts. Focusing solely on the prediabetic and T2DM cohorts, compared with the control, the relative reduction of the FBG, HbA1c levels, fasting insulin concentration and insulin sensitivity was 7.15, 7.00, 16.58, and 25.34% of their baseline values after supplementation [ 146 ]. A daily supplement dose greater than 10 g and for a minimum duration of 42 days was recommended for consistent improvement across the glycaemic indicators.…”
Section: Prebiotics Probiotics and Synbioticsmentioning
confidence: 99%
“…However, recent one study found that C57BL/6J mice fed a HF diet could be susceptible to liver cancer upon consumption of inulin (Singh et al, 2018). In clinical trials, it did not show adverse effects of inulin on liver function in human (Wang et al, 2019). The reason might be the duration of inulin treatment and HF diet.…”
Section: Discussionmentioning
confidence: 98%